Konversi Kayu Akasia (Acacia Mangium) Menjadi Bio-Oil Dengan Proses Pirolisis Menggunakan Katalis Ni/Lempung - Hardi, Rizka Aulia; Bahri, Syaiful; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Availability of fossil fuels as a non-renewable energy source has decreased due to the increase of energy consumption. Therefore, it is needed an alternative renewable energy sources, such as conversion of biomass derived from acacia mangium wood. Bio-oil can be produced by pyrolisis of Acacia mangium wood with catalyst Ni/clay. The purpose of this research are to produce bio-oil from acacia wood, to characterize of Ni/clay catalyst, to determine the effect of the impregnation of Ni metal in to clay and ratio of Ni/clay catalyst on the yield of bio-oil and to determine the physical and chemical characteristics of bio-oil. The pyrolysis was used 50 grams acacia wood, 500 ml silinap and Ni/clay catalyst with variations of the percentage of the Ni metal 0%, 1%, 2%, 3%, respectively and the variation ratio of Ni/clay catalyst of the biomass 3%, 5% and 7% with a stirring speed of 300 rpm and a temperature of 320ÂºC for 120 minutes. In this research, the highest yield was on the use of the catalysy Ni/clay 5% by weight of the metal content of 3% by 66,26%. Characterization of physical properties of bio-oil obtained in the form of density 1,004 gr/ml, 1,8452 cSt viscosity, acidity 71,6327 mg NaOH/gr sample, and the flash point 46oC, respectively.Keywords: Bio-oil, Pyrolysis, Catalyst Ni/Clay, Acacia mangium wood